2011
DOI: 10.1007/s11325-011-0606-x
|View full text |Cite
|
Sign up to set email alerts
|

Restless legs syndrome: a comprehensive overview on its epidemiology, risk factors, and treatment

Abstract: Clinicians' understanding of RLS enigma has recently improved due to the increased intensity of RLS research over the past decade. This review summarizes the current findings in the RLS field as well as providing guidelines for future RLS-related research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
93
0
10

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 156 publications
(115 citation statements)
references
References 207 publications
5
93
0
10
Order By: Relevance
“…RLS studies in adults have shown a higher prevalence in women; however, in a study of 10,523 children and adolescents, RLS rates were not different between males and females [17,21]. In adults, a higher rate of RLS in Caucasians has been shown in some studies, while other studies have shown no significant difference [22,23].…”
Section: Discussionmentioning
confidence: 90%
“…RLS studies in adults have shown a higher prevalence in women; however, in a study of 10,523 children and adolescents, RLS rates were not different between males and females [17,21]. In adults, a higher rate of RLS in Caucasians has been shown in some studies, while other studies have shown no significant difference [22,23].…”
Section: Discussionmentioning
confidence: 90%
“…1 RLS is diagnosed by the presence of an urge to move the limbs (typically the legs), which is usually but not necessarily accompanied by uncomfortable and unpleasant sensations. This urge to move will develop and intensify in periods of inactivity, worsen in the evening or night, is alleviated by some form of movement (such as stretching one's legs or walking), and is not solely accounted for by another medical or behavioral diagnosis (such as arthritis or leg cramps).…”
Section: Introductionmentioning
confidence: 99%
“…RLS affects &5-15 % of adults across Northern, Western and Southern European countries, and is sufficiently severe to require medical intervention in 2.5 % of cases [4]. RLS prevalence is higher in women than in men, and increases with increasing age [5].…”
Section: Introductionmentioning
confidence: 99%